2017
DOI: 10.1038/s41598-017-01038-2
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Characterization of Nigerian Propolis samples and Their Activity Against Trypanosoma brucei

Abstract: Profiling of extracts from twelve propolis samples collected from eight regions in Nigeria was carried out using high performance liquid chromatography (LC) coupled with evaporative light scattering (ELSD), ultraviolet detection (UV) and mass spectrometry (MS), gas chromatography mass spectrometry (GC-MS) and nuclear magnetic resonance spectroscopy (NMR). Principal component analysis (PCA) of the processed LC-MS data demonstrated the varying chemical composition of the samples. Most of the samples were active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 30 publications
7
57
0
3
Order By: Relevance
“…Then, they add salivary enzymes to the resins and mix it with beeswax, thereby forming propolis. Thus, the chemical composition of propolis varies with the geographical region, season, surrounding flora, and bee species [13,14,27,[29][30][31][32]. Over 500 chemical compounds have been identified from various samples of propolis from different regions and seasons [27,33].…”
Section: The Chemistry Of Propolismentioning
confidence: 99%
See 1 more Smart Citation
“…Then, they add salivary enzymes to the resins and mix it with beeswax, thereby forming propolis. Thus, the chemical composition of propolis varies with the geographical region, season, surrounding flora, and bee species [13,14,27,[29][30][31][32]. Over 500 chemical compounds have been identified from various samples of propolis from different regions and seasons [27,33].…”
Section: The Chemistry Of Propolismentioning
confidence: 99%
“…Owing to its long use in traditional medicine for treatment of infectious diseases and its reported antimicrobial activities [13,14], the chemical compositions and properties of propolis from diverse locations and floral origins are now being intensely investigated. Many scientific studies on propolis samples from different botanical sources, geographical regions, and seasons of collection have reported its pharmacological activities with results that point to its therapeutic potential against diseases caused by kinetoplastids [14][15][16][17][18][19][20][21][22][23][24]. This review contributes to this growing body of knowledge by bringing together the chemistry of propolis and its pharmacological activities, including its mode of action against the kinetoplastids.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic profile data have been utilized to distinguish diverse propolis from different geographic origins. Numerous metabolomic research works on the chemical compositions of propolis by various techniques, including thin layer chromatography [23], high-performance liquid chromatography (HPLC) [24], ultra-high-performance liquid chromatography coupled with mass spectrometry [25], and gas chromatography coupled with mass spectrometry [26], have been reported. The NMR technology as a significant spectroscopic method with fast, robust, reproducible, and non-destructive features can provide the unbiased structural information of organic samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, simple sample pretreatment, good stability, and short analysis time make it more suitable for high-throughput analysis. Recently, NMR-based metabolomics analysis was applied to a variety of propolis to study the characteristics and classification of southern Brazilian propolis [18], Nigerian propolis [24], as well as the discrimination of five regions: Asia, Brazil, Europe, Africa, and the Solomon Islands [27].…”
Section: Introductionmentioning
confidence: 99%
“…Gentiatibetine has certain anticonvulsant and brain protective effects (Peng 2016), gingediol (curcumin) could be used to treat cold and vomiting (Hatcher et al 2008), amarasterone A can reduce blood sugar (Catalan et al 1982), linolenic acid has been suggested to have antitumor properties (Huan et al 2012). Houpu lignan A has therapeutic effects on dyspepsia, abdominal distention, constipation and also has certain anti-cancer properties (Si et al 2002), albopetasin can relieve swelling and pain (Zhang 2009), ginsenoyne K could invig-orate the spleen and benefit the lung (He et al 1993), ambonic acid has antibacterial effect (Omar et al 2017), 7-hydroxycadalenal can relieve pain (State Administration of Traditional Chinese Medicine 2005), etc. These activities may attribute to the function of fermented Pinelliae Rhizoma.…”
mentioning
confidence: 99%